Secondary School Students’ Perception of ICT Use in EFL Classroom - Pardede, Parlindungan (JET (Journal of English Teaching), 2020)
Its huge potential to facilitate learning has made information and communication technology (ICT) use grow as one of the main advancements in the education sector in the 21st Century. This study aims at exploring secondary school students’ perceptions of ICT use in the EFL classroom. To achieve the objective, 197 students in 15 secondary schools located in Jakarta, Depok, and Bekasi were surveyed using a questionnaire. The data obtained were analyzed employing the descriptive analysis technique. The results showed that the participants’ perception was positive and high in some dimensions of ICT use in learning but low in one dimension. Positive and high perceptions were found in (1) the potentials of ICT use to increase learning interest and motivation; (2) the impacts of ICT use in learning; (3) ICT educational values; and (4) ICT use self-efficacy. It was also found that the participants used ICT more frequently for entertainment and socio-economic purposes than for learning activities. Finally, a majority of the participants thought taking formal ICT training to enable them to effectively use ICT in learning is not necessary.